METHODOLOGICAL GROUNDING OF ACME STRATEGY AND ACME TECHNOLOGY FOR THE SPECIALIST’S PRODUCTIVE ACTIVITIES IN SOCIONOMIC PROFILE - Gladkova, Valentina; Yujing, Ding (Educological discourse, 2019)
The article expounds the results of the acme strategy methodological foundation’s theoretical analysis and acme technology of productive activity’s theoretical analysis for socionomic specialists. It is noted that the most developed approach today is the functional role approach and personality-activity approach. Now scientists suggest subject-acmeological and acme synergetic approaches for analyzing the activities of socionomic specialists. The methodological principles of the creative personality development for the socionomic specialist are closely interconnected and form a system: intentional dynamism; invariance; individualization - collective identity; anthropological; studying the general in separate and through the separate; simultaneous study of person and his activities; the need to study person in a chain: individual – personality – subject of labor – individuality; systemic structural principle; historicism; humanism; development; unity of psyche and activity; reflection – of the subject; determinism – self-determinism. The considered methodological principles determine the methodological space of research, its specificity and orientation. They make possible the acme synergetic specificity of the socionomic specialist as a person who develops and improves the subjective nature of such development and self-improvement, which is aimed at the full disclosure of his or her inner potential, reaching the highest level. Relative to an individual person as a member of acme strategy society is a lifesupport system for acme values and the needs of self-development, self-actualization of individual, achievement of acme goal in the productive activity. The implementation of the result of acme strategies and its new environment entrance, in accord with the general acmeological law of development’s productive competence for specialist, manifests itself in the feedback process at the tactical, operational and strategic levels. The process of acme strategy’s development and implementation is designed to solve the problems of the formation and further improvement in professional structures as the foundation for building productive author’s activity system and achieving productive competence for specialist in it. Implementation of acme strategies in the professional activities for socionomic specialist is carried out using acme technologies. The distinctive feature of acme technology is the goal-setting process. In acme technology, the central problem is viewed from the position of the desired embodiment’s result which is in the spiritual product and properties of activity’s subjects and satisfies the requirements in advance. Acmeological technologies consider the multi-level interaction, relationships and interrelations. Important elements of acmetechnology are theoretical models of activity.